Efficient topology discovery algorithm for software‐defined networks. Issue 6 (1st November 2017) - Tarnaras, George; Athanasiou, Fanouria; Denazis, Spyros
Abstract : Software‐defined networking (SDN) already has an established presence in the networking industry as an emerging paradigm for designing network architectures, decoupling the control from the forwarding plane and offering a centralised way of network management. Cloud and enterprise infrastructure engineers have already adopted such techniques for building up their environments, deliberating the cost and flexibility advantages gained from this technology. However, smaller companies may choose a progressive replacement of their equipment due to operational and budget constraints. Hence, mixing equipment could lead up to hybrid SDN environments making network management even more complex. In this study, an event‐based generic topology discovery algorithm, capable of providing an efficient packet discovery mechanism using existing protocols in SDN networks, is proposed. For testing and evaluation purposes, address resolution protocol and link layer discovery protocol are being used to extract the information needed and reconstruct the topology to the controller. Implementation is accomplished using Internet Engineering Task Force's ForCES framework.